GERIATRIC SYNDROME IN ERNEST HEMINGWAY’S A CLEAN WELL LIGHTED PLACE (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2013)
This study is attempted to analyze geriatric syndrome found in the Ernest Hemingway’s short story entitled A Clean Well Lighted Place. The problems of the study are 1)How does Ernest see geriatric syndrome as reflected in A Clean Well Lighted Place? 2) How does Ernest Hemingway life relate to A Clean Well Lighted Place short story? To achieve the objectives of the study, I used qualitative descriptive research and biographical approach. The primary source of the data is the short storyA Clean Well Lighted Place. The data in this research are in the form of words, phrases, sentences, implicit meaning found in the short story, and other relevant source. Based on the analysis, it can be concluded thatmain theme of the story was a problem occurred in elder called geriatric syndrome.In addition, the story was a biography of Ernest Hemingway as it reflected Hemingway’s life.